2020
DOI: 10.1186/s40981-020-00372-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dexamethasone added to periarticular anesthetic infiltration and postoperative nausea and vomiting following total knee arthroplasty under general anesthesia: a retrospective observational study

Abstract: Background: Periarticular anesthetic infiltration (PAI) with a corticosteroid is a modality for pain control following total knee arthroplasty (TKA). Systemic corticosteroids are an established antiemetic for the prophylaxis of postoperative nausea and vomiting (PONV). The purpose of this retrospective observational study was to elucidate the relationship between dexamethasone added to PAI and PONV in patients who underwent TKA. Methods: Data from 435 patients who received PAI using ropivacaine with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Most postoperative nausea occurs during the first 24 h after surgery, and the intravenous administration of dexamethasone effectively prevents postoperative nausea [ 2 , 3 ]. Periarticular administration also had a postoperative antiemetic effect [ 23 ]. Another study showed that periarticular injection of corticosteroids had a similar antiemetic effect to intravenous administration [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most postoperative nausea occurs during the first 24 h after surgery, and the intravenous administration of dexamethasone effectively prevents postoperative nausea [ 2 , 3 ]. Periarticular administration also had a postoperative antiemetic effect [ 23 ]. Another study showed that periarticular injection of corticosteroids had a similar antiemetic effect to intravenous administration [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two independent investigators (Huang LY and Hu HH) screened the article titles and abstracts, identifying 36 studies as being potentially relevant. After 20 trials were excluded for failing to meet the selection criteria, the remaining 16 articles were included in the systematic review 4,5,9,15–17,24–33 …”
Section: Resultsmentioning
confidence: 99%
“…Two retrospective studies were not combined for synthetic control evaluation 32,33 . Ultimately, 14 RCTs met all the criteria and were assessed in the meta‐analysis 4,5,9,15–17,24–31 …”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether a cocktail injection containing a corticosteroid had an antiemetic effect by recording the number of patients who complained of nausea or by using antiemetic agents. Yano et al [ 14 ] and Ikeuchi et al [ 11 ] reported that fewer patients complained of nausea in a group that received a cocktail injection containing a corticosteroid. Conversely, Deng et al reported that corticosteroid-containing cocktail injections did not affect the prevalence of nausea and vomiting [ 15 ].…”
Section: Discussionmentioning
confidence: 99%